PENDAMPINGAN PROFESIONALISME KEGURUAN DI XAVIER LEARNING COMMUNITY, CHIANG RAI: MEMBANGUN KOMUNITAS PEMBELAJARAN - Budiraharjo, Markus; Wahyuni, Hanna Irma; Mawarni, Angelina Kusuma Jelita (Universitas Sanata Dharma, 2025)
Today’s venture capitalists will undergo a rational approach to open new schools so as to ensure long-term sustainability, in which alignment of goals, job divisions, revenue projections, student intakes, personnel placements, promotion strategies, to name a few, are organized as a concerted effort. Xavier Learning Community, a newly established Jesuit higher education institution, has come from a different direction and therefore, attempts to live against the modernist, accountability-based approach to opening a new educational enterprise. XLC Chiang Rai is nested in a socio-culturally, historically, and politically nuanced space of northern Thailand, where the hub of human trafficking, jade mining, drug abuse, Chinese-backed casinos, and prostitution are rampant. Given the dire contexts of the widening gaps between the majority of the Thai population and the self-subsistent tribal groups, as well as the limited access to quality education among the tribal groups living in remote regions of Thai borderlands, XLC has come to offer the young generation of those marginalized to enjoy affordable educational services. Drawing from a Husserlian perspective on purpose, intentionality, and harmony, this study reports a one-month activity to accompany XLC teachers in developing their consciousness in their service to support the Jesuit cause.